PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SIKAP PROFESIONAL GURU TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI PESERTA DIDIK KELAS X IPS DI SMA NEGERI 1 CEPER TAHUN AJARAN 2017/2018 - -, Rafika Erindaru -; -, Trisno Martono -; -, Budi Wahyono - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The aims of this research are: 1) to determine the influence of the principal?s leadership toward the learning achievement of economics in class X of SMA Negeri 1 Ceper, 2) to determine the influence of the teacher?s professional attitude toward the learning achievement of economics in class X of SMA Negeri 1 Ceper, and 3) to determine the influence of the principal?s leadership and the teacher?s professional attitude toward the learning achievement of economics in class X of SMA Negeri 1 Ceper. This research is a quantitative research. The population of the research was Class X in SMA Negeri 1 Ceper in the academic year of 2017/2018. The sampling technique used was Census Sampling. The number of samples was 64 respondents. The data collection methods used were interview questionnaire and documentation. The data analysis technique used was multiple linear regression. The result of the research shows that the equity of the multiple regression is Y = 7.148 + 0,604 X1 + 0,263 X2. The regression coefficient is positive which means that the principal?s leadership is positively and significantly influential toward the learning achievement of the students and the teacher?s professional attitude is positively and significantly influential toward the learning achievement of the students. It means that the better the principal?s leadership is, the higher the students? learning achievement will be and the higher the influence of the teacher?s professional attitude is, the higher the students? learning achievement will be. Based on the result of the research, it can be concluded that: (1) the principal?s leadership is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0.05 (0.000<0.05), (2) the teacher?s professional attitude is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0.05 (0.000<0.05), (3) the principal?s leadership and the teacher?s professional attitude simultaneously is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0.05 (0.000<0.05) and Adjusted R square value of 55.9%. It is shown that 55.9% of the learning achievement of the students is influenced by the the principal?s leadership and the teacher?s professional attitude, while the rest which is 44.1% is influenced by other factors not mentioned in this research